2020
DOI: 10.20473/mog.v28i12020.24-31
|View full text |Cite
|
Sign up to set email alerts
|

The outcome of Manchester operation in cervical elongation patients with pelvic organ prolapse at Dr. Soetomo Hospital, Surabaya from January 2015 to June 2017

Abstract: Objectives: the aim of this study is to report the outcome of Manchester operation in cervical elongation patients with pelvic organ prolapse at Dr. Soetomo Hospital, Surabaya from January 2015 to June 2017.Case Report: During January 2015 until June 2017 there were seven patients already performed Manchester operation, however only four patients routine control. In all four cases, three cases were obtained with cervical elongation with a pelvic organ prolap (POP) and one case with cervical elongation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Physical problems they can encounter include pain, sexual dysfunction, discharge (abnormal fluid from the vagina), sensation and heavy acidification in the vagina, difficulty walking and sitting, infection, and decay of tissues. Furthermore, the respondents also did not understand that women of all ages can experience uterine prolapse, where prolapse is more common in women with grande multipara and old age (Nizomy et al, 2013). Contrarily, after the health education using android, all respondents (100%) had good knowledge in correctly answering questions about how women with prolapse uteri can experience physical and psycho-social problems.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Physical problems they can encounter include pain, sexual dysfunction, discharge (abnormal fluid from the vagina), sensation and heavy acidification in the vagina, difficulty walking and sitting, infection, and decay of tissues. Furthermore, the respondents also did not understand that women of all ages can experience uterine prolapse, where prolapse is more common in women with grande multipara and old age (Nizomy et al, 2013). Contrarily, after the health education using android, all respondents (100%) had good knowledge in correctly answering questions about how women with prolapse uteri can experience physical and psycho-social problems.…”
Section: Discussionmentioning
confidence: 97%
“…Uterine prolapse is one of the problems of reproductive health (Shrestha et al, 2014). Women with prolapse can experience physical and psychosocial problems (Nizomy et al, 2013). The physical issues they encounter include pain, sexual dysfunction, discharge (abnormal fluid from the vagina), sensations and feelings of heaviness in the vagina, difficulty walking and sitting, infection, and tissue decay.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiologically, pelvic organ prolapse is acknowledged to affect approximately 50% of women who have undergone childbirth (Weintraub et al, 2020). Although the precise prevalence of uterine prolapse still remains ascertain, a study conducted at Dr. Soetomo general hospital Surabaya through 2007 to 2011 reported that among all cases of pelvic organ prolapse, uterine prolapse predominated constituting 66% of the total population studied (Nizomy et al, 2013).…”
Section: Introductionmentioning
confidence: 99%